A study of surgical pathology of thyroid lesions - Jain, Shikha S.; Dagar, Priyanka M.; Dagar, Munish K. (International Journal of Research in Medical Sciences, 2025)
Background: Thyroid lesions commonly present as midline neck swelling that move with deglutition. These lesions are broadly divided into non-neoplastic and neoplastic. Non-neoplastic can be developmental, inflammatory, hyperplastic. Neoplastic are stratified into benign tumors, low risk neoplasms and malignant neoplasms. Most of these lesions are amenable to surgical resection. This study aims to analyse the demographic features and histopathological spectrum of surgically resected thyroid lesions. Methods: A total of 55 surgically resected thyroid specimens received in Department of Pathology, World College of Medical Sciences and Research Hospital were included. Demographic and clinical details were obtained from departmental records. Histopathological examination was conducted according to standard protocol. Percentages and simple frequency tables were used for analysis. Results: Age ranged from 20-97 years. Maximum number of cases were reported in 3rd to 5th decade. Female: male ratio was 5.1:1. Non-neoplastic lesions were 29 (52.72%) and 26 (47.27%) neoplastic lesions were encountered in which colloid goitre and papillary carcinoma thyroid were the commonest ones respectively. Conclusions: Non-neoplastic lesions were slightly more common than neoplastic lesions. Ultrasonography (USG), thyroid function test and fine needle aspiration cytology (FNAC) give a clue but study of histomorphologic features is the final confirmatory test guiding a clinician towards further patient management.